Investigation of Social, Emotional Loneliness Levels and Eating Behaviors of Nursing Students - Burcu Cengiz; Dijle Ayar; Gülcihan Arıkan; İlknur Bektaş (Dokuz Eylul University, 2020)
Background: Loneliness is increasing gradually in early adulthood individuals and various abnormal eating behaviors may be encountered to cope with this. Objectives: The aim of this study was to investigate the social, emotional loneliness levels and eating behaviors of nursing students. Methods: The sample of this descriptive and cross - sectional study consisted of 1000 students in a nursing faculty in İzmir. The data of the study were collected by using ''Descriptive Information Form", Social and Emotional Loneliness Scale", "REZZY Eating Disorders Scale" and ORTO-11 Scale. Data were evaluated by descriptive statistics, t test and one-way variance analysis. Results: In this study, 44.0% of the students stated that they met with their family three days a week for three days and 53.7% of them met with their friends by phone every day. In the study, it was determined that 31.6% of nursing students exhibited risky behaviors in terms of eating disorders. The mean total score of the REZZY eating disorders scale of the nursing students was 1.09 ± 1.10; the mean total score of the ORTO-11 scale was 26.55 ± 4.47; the mean total score of social and emotional loneliness was 43.19 ± 15.18. Conclusion: In this study, it was determined that the level of social and emotional loneliness of the students who could not share their problems with their family or friends was high. As the level of education in the school has increased, the risks of eating disorders and level of loneliness have been decreased. Therefore, there is a need for interventional studies aiming at adaptation of the first and second year nursing students to their new environment or increasing their social environment and sharing, especially separated from their families or their social environment.